Relationship of Body Composition with the Strength and Functional Capacity of People over 70 Years (2020)
ABSTRACT: Abstract: Background: Aging is a multifactorial physiological phenomenon, in which a series of changes in the body composition occur, such as a decrease in muscle mass and bone mineral density and an increase in fat mass. This study aimed to determine the relationship of muscle mass, osteoporosis, and obesity with the strength and functional capacity of non-dependent people over 70 years of age. Methods: A cross-sectional study was designed, whose study population was all people aged over 70 years, living independently and attending academic and recreational programs. Muscle strength and functional capacity of the participants were assessed by isometric exercises of lower and upper limbs and by four tests taken from the Senior Fitness Test, respectively. Bone mineral density, total mass, fat mass, total lean mass, arms lean mass, legs lean mass, and appendicular lean mass (ALM) was calculated by dual energy X-ray absorptiometry. Differences in muscle strength and functional capacity, according to the sex, muscle mass, mineral bone density and fat mass, were measured by χ 2 test, independent samples Student’s t-test, analysis of covariance and a 2-factor analysis of covariance; Results: 143 subjects were included in the study group. Men and women with an adequate amount of ALM adjusted for body mass index (BMI) had a maximal dynamic biceps strength in a single repetition, a maximal isometric leg extension strength, a maximal dynamic leg extension strength in a single repetition, a maximum right hand grip strength and maximum hand grip strength (the highest). Significantly higher values were observed in the maximal isometric biceps’ strength in men with osteoporosis. Obese men had less isometric strength in the biceps and took longer to perform the chair stand test; Conclusions: Men and women with an adequate amount of ALM adjusted for BMI obtained better results in tests of muscle strength and functional capacity. However, osteoporosis and obesity are not related to these parameters.